Harnessing Fuzzy Delphi: Designing the innovative DiD-Art application - Salleh , Maznah; Khairani , Mohd Zahuri; Mohd Rafee , Yakup; Mohamad, Shahrul Amri (Environment-Behaviour Proceedings Journal, 2025)
This research aimed to develop an android-based drawing art application (DiD-Art). Using the Fuzzy Delphi Method, researchers surveyed 20 experts to evaluate seven constructs and 37 items for the application. The findings revealed expert agreement on all constructs and items, meeting the three Fuzzy conditions. The research resulted in a design framework for the DiD-Art application, which will serve as a teaching and learning material for Visual Art Education teachers. This study leverages digital technology to enhance accessibility and impact art education. Thus, future research could focus on implementing and evaluating the application’s effectiveness in real classroom settings